Influence of the Microstructure of the Initial Material on the Zn Wires Prepared by Direct Extrusion with a Huge Extrusion Ratio - Jaroslav Čapek; Lukáš Kadeřávek; Jan Pinc; Jaromír Kopeček; Ladislav Klimša (Metals, 2021)
In this study, we prepared zinc wires with a diameter of 250 µm by direct extrusion using an extrusion ratio of 576. We studied the influence of the extrusion temperature and microstructure of the initial Zn billets on the microstructural and mechanical characteristics of the extruded wires. The extrusion temperature played a significant role in the final grain size. The wires extruded at 300 °C possessed a coarse-grained microstructure and the shape of their tensile stress–strain curves suggested that twinning played an important role during their deformation. A significant influence of the initial grain size on the final microstructure was observed after the extrusion at 100 °C. The wires prepared from the billet with a very coarse-grained microstructure possessed a bimodal grain size. A significant coarsening of their microstructure was observed after the tensile test. The wires prepared from the medium-grained billets at 100 °C were relatively coarse-grained, but their grain size was stable during the straining, resulting in the highest ultimate tensile strength. This preliminary study shows that strong attention should be paid to the extrusion parameters and the microstructure of the initial billets, because they significantly influence the microstructure and mechanical behavior of the obtained wires.